PENGARUH PENGETAHUAN ANGGOTA TENTANG KOPERASI DAN KUALITAS PELAYANAN TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) KANTOR WILAYAH KEMENTRIAN AGAMA PROVINSI RIAU - Sulastri, Lasti Sulastri Lasti; ', Caska; ', Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of the research was to know whether there is any influence of members knowledge about cooperative and quality of the service on members participation at Koperasi Pegawai Republik Indonesia (KPRI) Of Religion Ministry Department, Province Of Riau. This research was done on June 2014. The population of the research was the entire member of the cooperative department (KPRI) of religion ministry department, province of Riau. The total of the sample was 289 members. The sample which is used was 72 people and technique of data collection was systematic random sampling technique. The technique of data analysis was by using SPSS 16.0 version. The conclusion of the test F (F-test) of the influence of members knowledge about cooperative and quality service on members participation was found 26,695. Meanwhile , F-table was found 3,13 . so the researcher found that F hitung > F table . it means that there is a influence of members knowledge about cooperative and quality service on members participation. R2 scale was found 0,436 which is mean the variable of members’ knowledge about cooperative and quality service 43,6 % as known as variability from the member participation and the rest is influence by the others variables that were not belong for this research . the similiarity of the double regression was found Ŷ= 5,635 +0,040 X1 + 0,295 X2.Keywords : participation, members’ knowledge and service quality